2012
DOI: 10.2527/jas.2011-3874
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation with an organic source of selenium on characteristics of semen quality and in vitro fertility in boars1

Abstract: Semen characteristics in boars fed organic or inorganic sources of Se were assessed in 3 experiments. Crossbred boars were randomly assigned at weaning to 1 of 3 dietary treatments: I) basal diets with no supplemental Se (control), II) basal diets with 0.3 mg/kg of supplemental Se from an organic source (Sel-Plex, Alltech Inc., Nicholasville, KY), and III) basal diets supplemented with 0.3 mg/kg of supplemental Se from sodium selenite (Premium Selenium 270, North American Nutrition Co. Inc., Lewisburg, OH). Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 22 publications
5
21
0
Order By: Relevance
“…Similar results were reported for humans (16,25), boars (18,23,24,34), and turkeys (33) after supplementation with selenium and vitamin E. To our knowledge, no studies have been carried out on the influence of oral selenium supplementation on semen quality in the dog.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar results were reported for humans (16,25), boars (18,23,24,34), and turkeys (33) after supplementation with selenium and vitamin E. To our knowledge, no studies have been carried out on the influence of oral selenium supplementation on semen quality in the dog.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore a higher resistance to oxidative stress should be expected when selenium is provided. A positive effect of selenium on sperm concentration and morphology has been also reported by other authors in men (26,32) and various animal species (18,23,24,33,34,37). On the contrary, some studies have reported that there were no positive effects of selenium supplementation on sperm quality either in humans (12,15) or boars (13).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Also the results obtained in the present study showed that selenium concentration in the boar ejaculate was higher in the experimental group in comparison to control group after the 90-day feeding period. Also Speight et al (2012) observed the increased sperm motility after addition of 0.3 mg of Se to the diet. Moreover, it was estimated that vitamin E also positively affectes sperm quality reducing the percentage of the abnormal sperm at the dose of 300 and 450 mg · kg -1 (Moraes et al, 2010;Xia et al, 2012).…”
Section: Discussionmentioning
confidence: 78%
“…Various management strategies, such as manipulating nutrition of the adult boar, have been used to increase reproductive performance (Estienne et al 2008, Speight et al 2012. While management of the sexually mature animal may influence reproductive performance, it is now evident that management of the boar early-in-life, such as during the suckling period, may have profound effects as well.…”
Section: Mj Estiennementioning
confidence: 99%